Surface fluorination of lithium metal with elemental fluorine for use as anode in lithium metal batteries

CN116829508BActive Publication Date: 2026-10-09LIFT ENERGY SRL
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202280010388.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-01-15
Filing Date
2022-01-11
Publication Date
2026-10-09
Estimated Expiration
2042-01-11

AI Technical Summary

Technical Problem

在任何情况下,都形成额外的和相当复杂的副产品

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004341418950000011
    Figure HDA0004341418950000011
  • Figure HDA0004341418950000021
    Figure HDA0004341418950000021
  • Figure HDA0004341418950000031
    Figure HDA0004341418950000031
Patent Text Reader

Abstract

Surface fluorination method of lithium metal using elemental fluorine. Thereby, a homogeneous LiF surface layer without impurities is formed over the entire surface of the Li metal. This highly reproducible process can also be carried out on a large scale, so that a material can be obtained which can be advantageously used as anode in lithium batteries, since it ensures significantly higher performance than those obtained not only by using lithium metal as anode, but also lithium metal anodes provided with a LiF layer, the formation of which is formed in situ from organic or inorganic fluorine reagents. Surface fluorination method of lithium metal using elemental fluorine. Thereby, a homogeneous LiF surface layer without impurities is formed over the entire surface of the Li metal. This highly reproducible process can also be carried out on a large scale, so that a material can be obtained which can be advantageously used as anode in lithium batteries, since it ensures significantly higher performance than those obtained not only by using lithium metal as anode, but also lithium metal anodes provided with a LiF layer, the formation of which is formed in situ from organic or inorganic fluorine reagents. Surface fluorination method of lithium metal using elemental fluorine. Thereby, a homogeneous LiF surface layer without impurities is formed over the entire surface of the Li metal. This highly reproducible process can also be carried out on a large scale, so that a material can be obtained which can be advantageously used as anode in lithium batteries, since it ensures significantly higher performance than those obtained not only by using lithium metal as anode, but also lithium metal anodes provided with a LiF layer, the formation of which is formed in situ from organic or inorganic fluorine reagents.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for surface fluorination of lithium metal with elemental fluorine, which is used as an anode in lithium metal batteries. Background Technology

[0002] Lithium metal batteries (LMBs) can be classified as primary batteries or secondary batteries depending on whether they are rechargeable.

[0003] High-energy-density primary LMBs were conceived in the 1970s and used in watches, computers and portable medical devices.

[0004] Typically, rechargeable batteries have a lower energy density than primary batteries. However, rechargeable batteries have a wider range of applications because they are rechargeable.

[0005] The first lithium-ion batteries (LMBs), designed by Nobel laureate Stanley Wittingham in Esso, used lithium metal as the negative electrode and TiS2 as the positive electrode. Research stalled until the 1980s due to the danger of dendrite formation on the lithium anode surface. In the late 1970s, lithium-ion batteries (LIBs), also known as "rocking chair" batteries, were studied. These consisted of a series of layered and interleaved materials for both the anode and cathode. According to charge-discharge theory, lithium ions are transferred from the cathode to the anode during charging without being reduced to lithium metal atoms, thus avoiding dendrite formation.

[0006] In 1991, LIBs first appeared on the market, revolutionizing and simultaneously promoting the expansion of the electronics market.

[0007] The best-performing LIBs are those with graphite anodes. However, the energy density of such batteries has reached its limit and cannot be increased further. Therefore, research has returned to and focused on LMBs in order to obtain batteries with higher energy densities.

[0008] The corrosive chemistry of lithium metal has raised several issues, one of the most pressing being the formation of lithium dendrites, which poses a serious safety risk due to the inherent properties of lithium atoms, namely their high diffusion barrier. Indeed, when lithium metal is deposited on the anode, dendrites tend to form simultaneously on the holes in the metal plate formed during the initial stripping process and on the surface of the lithium anode during the initial plating step.

[0009] Repeated plating and stripping steps, namely lithium metal deposition and lithium ion dissolution, result in the formation of numerous dendrites and low coulombic efficiency (CE) on the anode surface.

[0010] The continuous growth of Li dendrites can lead to penetration and damage of the separator, resulting in short circuits in the battery, high-current discharge, high-heat development, and even explosion.

[0011] Furthermore, the rapid and irregular dissolution of lithium dendrites near the active site causes the dendritic lithium to separate from the metal matrix, creating so-called "dead Li" or electrically isolated lithium metal. This dead Li remains encased in a thick layer of the SEI (solid-electrolyte interface), which comprises both organic and inorganic lithium species, during repeated volume changes in the electrolyte, thus deactivating it. This results in the loss of active lithium in the electrode and consequently reduces battery capacity.

[0012] It has been shown that lithium fluoride in the SEI layer is a key component in preventing dendrite formation and growth in LMBs, because Li + The ions exhibit a higher diffusion rate through LiF than through Li2(CO3)2 because the barrier energy of the former is 0.09 V lower than that of the latter.

[0013] There are many methods for obtaining the LiF layer by applying a pre-formed LiF layer and by forming lithium fluoride in situ.

[0014] Among those of the first type, for example, the method proposed by Peng et al., in which a LiF-rich layer comprising nanoscale cross-linked LiF domains is applied to the anode to prevent collateral reactions between the Li metal and the electrolyte, resulting in long-term cycling of the lithium metal anode.

[0015] Another approach of the first type was proposed by Hou et al., who envisioned applying an artificial SEI layer rich in LiF and Li3N to the Li anode, which could stabilize the lithium metal and electrolyte, thereby enhancing compatibility at the interface on the lithium metal anode.

[0016] The second type of method for obtaining LiF was proposed by Lang et al., which involves the in-situ reaction of lithium metal with a solution of polyvinylidene fluoride (PVDF) in dimethylformamide (DMF) to create an anode coated with a LiF layer. This SEI film is able to suppress dendrite formation and reduce side reactions between lithium metal and carbonate-based electrolytes (see R. Wang et al., review, Journal of Energy Chemistry 48 (2020) 145-159; https: / / doi.org / 10.1016 / j.jechem.2019.12.024).

[0017] There is also a first-type method that applies a LiF layer by chemical vapor deposition (CVD) (J. Koh et al., Thin Solid Films 119-125; https: / / doi.org / 10.1016 / j.tsf.2019.01.48).

[0018] Most of the second type of LiF formation on the anode via chemical reaction considers indirect fluorination through the decomposition of fluorinated organic compounds, such as the method of Lang et al. mentioned in the aforementioned review by Wang et al., which allows for the formation of LiF and also allows for the formation of further layers of various types of carbon compounds. In any case, these methods are difficult to scale up because they require very high temperatures and do not always yield reproducible results.

[0019] For example, S. Sun et al. disclosed a protective SEI layer formed by a LiF / defluorinated polymer composite material, which is uniformly deposited on lithium metal by roll pressing PTFE Li as a sacrificial layer. Thus, the SEI layer formed using this method consists of an innermost layer in contact with lithium-rich lithium metal, while the outermost layer on the electrolyte side is composed of a polymer material consisting of a mixture of polyenes and unsaturated fluorinated polymers (S. Sun et al., J. Mater. Chem. A 2020, 8, 17729-17237; DOI: 10139 / d0ta05372d).

[0020] Alternatively, D. Lin et al. disclosed a method for forming a protective layer of LiF by treating it with Freon gas R134A (1,1,2,2-tetrafluoroethane) and Li metal at a temperature not lower than 150°C. First, (CH2F-CF2) is formed. - Li + Then, through α or β elimination, LiF is obtained. In any case, additional and rather complex byproducts are formed. To reduce the amount of these byproducts, the work must be carried out at 180 °C (D. Lin et al., Nano letters 2017, 17, 3731-3737; DOI: 10,121 / acs.nanolett7b0120).

[0021] Instead, Zhao et al. conceived of using the fluorinated polymer CYTOP as a source of fluorine for forming the LiF layer on the anode. CYTOP's degradation at 350°C releases fluorine, which then contacts the Li anode, forming a LiF coating on the Li anode (J. Zhao et al., J. Am. Chem. Soc. 2017, 139, 11550-11558. DOI: 10.1021 / Jacs.7b05251).

[0022] Another method described by He et al. for forming lithium fluoride coatings on the anode involves using inorganic fluorinating agents such as nitrogen trifluoride (NF3) instead of organic fluorinating agents. Again, in this case, to obtain a uniform LiF layer, operation must be carried out at a high temperature of not less than 180°C, and in any case, the LiF layer lacks sufficient resilience because it undergoes many morphological changes during the plating steps, becoming indistinguishable from lithium metal, and this occurs after 1.5 cycles. (M. He et al., PNAS / January 7, 2020 / Vol. 117 / 1 / 7 3-79) www.pnas.org / cgi / doi / 10.1073 / pnas.1911017116 ). Summary of the Invention

[0023] Alternatively, the applicant has discovered a safe surface fluorination method for lithium metal, which allows a uniform layer to be obtained on a lithium anode, enabling the lithium anode to withstand numerous cycles.

[0024] With proper adjustment of operating conditions, this method is easily scalable, adaptable, and even continuously operable. Furthermore, unlike the aforementioned processes obtained through in-situ production of fluorine, the method proposed in this invention does not involve the emission of byproducts generated by the decomposition of precursors using fluorine. Moreover, fluorine is already widely used industrially in the fluorinated materials industry.

[0025] Specifically, the method involves fluorinating a lithium metal surface with fluorine gas at a pressure between 0.01 mbar and 10 bar and a temperature between -78°C and 180°C.

[0026] Inactive diluent gases can be used with fluorine under reaction conditions with pressures between 0.01 mbar and 10 bar. The inactive gas under these reaction conditions can be, for example, an inert gas, particularly He or Ar; a perfluoroalkane, such as CF4 or C2F6; or a fluorinated inactive gas, such as sulfur hexafluoride, SF6. Using this methodology, a gas mixture containing fluorine (pure or diluted) can be fed into the fluorination reactor at a flow rate between 0.05 NL / h and 100 NL / h. However, those skilled in the art can appropriately select the diluent gas according to the operating conditions so that it does not interfere with the surface fluorination process.

[0027] Another object of the present invention is a Li metal anode for lithium metal batteries (LMBs) with a surface-coated LiF-based layer, wherein the layer is substantially composed of LiF and is preferably obtained by the method according to the invention.

[0028] Finally, another object of the present invention is a Li metal battery (LMB) incorporating the anode subject of the present invention. Attached Figure Description

[0029] Figure 1 The potential trend over time of a surface-LiF-coated lithium metal cyclate anode according to the method described in Example 1 is described.

[0030] Figure 2 Electrochemical impedance spectroscopy (EIS) spectra of the LiF-coated anode before and after cycling, under the operating conditions of Example 1, are shown.

[0031] Figure 3 The potential trend over time of a surface-LiF-coated lithium metal cyclic anode according to the method described in Example 2 is described.

[0032] Figure 4 The potential trend over time of a surface-LiF-coated lithium metal cyclic anode according to the method described in Example 3 is described.

[0033] Figure 5 The potential trend over time of a surface-LiF-coated lithium metal cyclic anode according to the method described in Example 4 is described.

[0034] Figure 6 The potential trend over time of a surface-LiF-coated lithium metal cyclic anode according to the method described in Example 5 is described.

[0035] Figure 7 The potential trend over time of a surface-LiF-coated lithium metal cycling anode according to the method described in Example 6 is described.

[0036] Figure 8 The potential trend over time of a surface-LiF-coated lithium metal cyclic anode according to the method described in Example 7 is described.

[0037] Figure 9 The potential trend over time of a surface-LiF-coated lithium metal cyclic anode according to the method described in Example 8 is described.

[0038] Figure 10 The potential trend over time of a surface-LiF-coated lithium metal cyclic anode according to the method described in Example 9 is described.

[0039] Figure 11 The potential trend over time of a surface-LiF-coated lithium metal cyclic anode according to the method described in Example 10 is described.

[0040] Figure 12The potential trend over time of a surface-LiF-coated lithium metal cyclic anode according to the method described in Example 11 is described.

[0041] Figure 13 The potential trend over time of a surface-LiF-coated lithium metal cyclic anode according to the method described in Example 12 is described.

[0042] Figure 14 The potential of a surface-LiF-coated lithium metal anode, cyclically used in a complete cell with an LFP cathode according to the method reported in Example 13, is shown as a trend over time.

[0043] Figure 15 The specific charge-discharge capacity and coulombic efficiency as a function of time of a surface-LiF-coated lithium metal anode cyclically in a complete cell with an LFP cathode according to the method reported in Example 13 are shown. Detailed Implementation

[0044] For the purposes of this invention, the definition of "method includes" does not exclude the presence of additional steps beyond those explicitly mentioned after this definition.

[0045] The definition "a method consists of..." means that such a method excludes the existence of any steps other than those explicitly reported after this definition.

[0046] Preferably, the method of the present invention consists of the surface treatment using pure fluorine gas or fluorine gas diluted with an inactive gas.

[0047] The "substantially made of LiF" layer of the anode according to the invention means that the layer contains more than 92% by weight, preferably more than 95% by weight, and even more preferably more than 98% by weight of LiF.

[0048] The anode material of the present invention is preferably obtained by means of the method according to the present invention.

[0049] The method according to the invention is preferably carried out at a temperature between -30°C and 130°C, more preferably between 0°C and 90°C, and even more preferably between 15°C and 80°C.

[0050] The pressure is preferably between 0.01 mbar and 1000 mbar, more preferably between 0.5 mbar and 200 mbar.

[0051] The amount of fluorine added in the method of the present invention is preferably 2.5 × 10⁻⁶. -9 mol fluorine / cm 2 Lithium metal with 0.51 mol fluorine / cm 2 Among lithium metals, a more preferred value is 5.08 × 10⁻⁶. -9mol fluorine / cm 2 Lithium metal with 0.255 mol / cm³ of fluorine 2 Between lithium metals.

[0052] Using the method of the present invention, LiF-coated anodes can be obtained in a very short time ranging from 1 second to 40 minutes, preferably between 1 minute and 30 minutes.

[0053] The anode obtained by the method of the present invention is very stable and can withstand many cycles, such as more than 2,000 cycles of stripping and plating.

[0054] For this reason, the batteries of the present invention, which include such anodes, can be advantageously used in the automotive industry, as well as in other energy storage applications ranging from small to large scale.

[0055] In forming a battery according to another purpose of the invention, the choice of electrolyte is not critical. In fact, solvents belonging to, but not limited to, the families of cyclic and linear carbonates (dimethyl carbonate, ethylene carbonate, propylene carbonate, diethyl carbonate, etc.), ethers (ethylene glycol dimethyl ether (glyme), dioxolane (DOL), dimethyl ether (DME), polyethylene glycol, polyethylene oxide, tetrahydrofuran, etc.), sulfoxides (e.g., dimethyl sulfoxide (DMSO), etc.), ionic liquids, and ionic salts (e.g., (etc.), polymer gels, polymers, conductive ceramics (e.g., Li), 2+2x Zn 1-x GeO4, Lithium Lanthanum Zirconium Oxide (Li7La3Zr2O) 12Lithium salts include, but are not limited to, LiClO4, LiNO3, LiPF6, LiFSI, LiTFSI, LiBF4, and LiAsF6. Preferably, an electrolyte is used consisting of 1M LiPF6 in diethyl carbonate: ethylene carbonate (1:1, by volume) or 1M LiTFSI in 1,3-dioxolane:1,2-dimethoxyethane (1:1, by volume), with 1-3% by weight of LiNO3 added. However, according to a preferred embodiment of the invention, as the electrolyte, an electrolyte mixture obtained by mixing 1M LiPF6 in diethyl carbonate: ethylene carbonate (1:1, by volume) or 1M LiTFSI in 1,3-dioxolane:1,2-dimethoxyethane (1:1, by volume) with LiNO3, ethylene fluoride carbonate, vinylene carbonate, and other stabilizing additives of SEI is used. The choice of cathode is not critical to the battery subject matter of this invention, so conventional types can be used. These choices include, but are not limited to, cathodes such as: transition metal oxides (lithium cobalt oxide, LiNiO2, lithium nickel cobalt aluminum oxide, lithium manganese oxide, nickel manganese cobalt, lithium titanium oxide, Fe2O3, Fe3O4, TiO2, CuO, NiO, MnO2, SnO2, etc.), semiconductor oxides (SiO2, Al2O3, etc.), transition metal fluorides (FeF2, FeF3, CoF3, CuF2, NiF2, BiF3, etc.), transition metal chlorides (FeCl3, FeCl2, NiCl2, CoCl2, NiCl2, CuCl2, AgCl2, AgCl, etc.), transition metal sulfides (Ni3S2, FeS2, CoS2, TiS2, TiS3, CuS, Cu2S, VS2, etc.), sulfur (S), carbon sulfur (CS), and fluorinated carbon (C). x F y), iodine (I), phosphorus and transition metal phosphides (CoP, Ni2P, WP, MoP, CoP, FeP, Cu3P, NiP2, etc.), carbonaceous metals (carbonaceous) Metals (graphene, graphite, nanosheets, carbon black, acetylene black, Ketjen black, multi-walled carbon nanotubes, single-walled carbon nanotubes, carbon nanofibers, etc.), phosphates (LMP, LFP, LCP, LiFeSO4F, LiVPO4F, etc.), transition metals (Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Cd, Hf, Ta, W, Re, Os, Ir, Pt, Au, Hg, Rf, Db, Sg, Bh, Hs, Mt, Ds, Rg, Cn, etc.), SOCl2, SO2Cl2, SO2, Ag2CrO4, silver vanadium oxide (SVO), copper oxyphosphate, PbCuS, bismuth lead, selenium, and any combination of air. Pre-lithiated cathodes are preferably used, such as lithium iron phosphate (LFP), lithium cobalt oxide (LCO), lithium manganese oxide (LiMn2O4), and lithium cobalt oxides containing nickel, manganese, and aluminum (NMC, NCA). Some examples of patents using the aforementioned cathodes are EP2983230A1, US9755234B2, US7722848B2, US6103213A, WO2016106321A1, and WO2007034243A1.

[0056] The following examples, given for illustrative and non-limiting purposes, also include the following embodiments.

[0057] Example 1: Fluorination at RT (25°C) and 100 mbar for 3 minutes

[0058] A lithium disk with a thickness of 1 mm and a diameter of 15 mm was inserted into the fluorination reactor. Fluorine gas (F2) was injected into the reactor at room temperature and a pressure of 100 mbar for 3 minutes. The resulting fluorinated lithium anode was then subjected to a pressure of 2 mA / cm². 2 and 1mAh / cm 2 In the lower cycle (plating-stripping), 1M LiTFSI in 1,3-dioxolane:1,2-dimethoxyethane (1:1, by volume) with 1-3% by weight of LiNO3 added was used as the electrolyte. Figure 1 The trend of potential over time is shown. Figure 2 Electrochemical impedance spectroscopy (EIS) spectra are shown before and after three cycles.

[0059] Example 2: Fluorination at RT (25°C) for 3 minutes at 29 mbar, with pre-cycling.

[0060] A lithium disk with a thickness of 1 mm and a diameter of 15 mm was placed in the fluorination reactor, resulting in a reduced volume. Fluorine gas (F2) was injected into the fluorination reactor at room temperature and a pressure of 29 mbar for 3 minutes. One of the fluorinated lithium anodes obtained was then subjected to a pressure of 0.1 mA / cm². 2 and 0.2mAh / cm 2 The next cycle is repeated 1.5 times (plating-stripping-plating), followed by 2mA / cm. 2 and 1mAh / cm 2 In the next cycle, 1M LiTFSI in a 1,3-dioxolane:1,2-dimethoxyethane (1:1, by volume) electrolyte with 1-3 wt% LiNO3 added was used. The graph showing the trend of potential over time is shown in... Figure 3 middle.

[0061] Example 3: Fluorination at 80°C and 35 mbar for 3 minutes, with pre-cycling.

[0062] A lithium disk with a thickness of 1 mm and a diameter of 15 mm is placed in the fluorination reactor, resulting in a reduced volume. Fluorine gas (F2) is injected into the fluorination reactor at 80°C and a pressure of 35 mbar for 3 minutes. The resulting fluorinated lithium anode is then subjected to a pressure of 0.1 mA / cm². 2 and 0.2mAh / cm 2 The next cycle is repeated 1.5 times (plating-stripping-plating), followed by 2mA / cm. 2 and 1mAh / cm 2 In the next cycle, 1M LiTFSI in a 1,3-dioxolane:1,2-dimethoxyethane (1:1, by volume) electrolyte with 1-3 wt% LiNO3 added was used. The graph showing the trend of potential over time is shown in... Figure 4 middle.

[0063] Example 4: Fluorination at 80°C and 35 mbar for 3 minutes, with pre-cycling.

[0064] A lithium disk with a thickness of 200 micrometers and a diameter of 15 millimeters was placed in the fluorination reactor, resulting in a reduced volume. Fluorine gas (F2) was injected into the fluorination reactor at 80°C and a pressure of 35 mbar for 3 minutes. The resulting fluorinated lithium anode was then subjected to a pressure of 0.1 mA / cm². 2 and 0.2mAh / cm 2 The next cycle is repeated 1.5 times (plating-stripping-plating), followed by 2mA / cm. 2 and 1mAh / cm 2In the next cycle, 1M LiTFSI in a 1,3-dioxolane:1,2-dimethoxyethane (1:1, by volume) electrolyte with 1-3 wt% LiNO3 added was used. The graph relating the potential trend is shown in... Figure 5 middle.

[0065] Example 5: Fluorination at RT (25°C) and 18 mbar for 30 minutes, with pre-cycling.

[0066] A lithium disk with a thickness of 1 mm and a diameter of 15 mm was placed in the fluorination reactor, resulting in a reduced volume. Fluorine gas (F2) was injected into the fluorination reactor at room temperature and a pressure of 6 mbar for 30 minutes. The resulting fluorinated lithium anode was then subjected to a pressure of 0.1 mA / cm². 2 and 0.2mAh / cm 2 The next cycle is repeated 1.5 times (plating-stripping-plating), followed by 2mA / cm. 2 and 1 / cm 2 In the next cycle, 1M LiTFSI in a 1,3-dioxolane:1,2-dimethoxyethane (1:1, by volume) electrolyte with 1-3 wt% LiNO3 added was used. The graph showing the trend of potential over time is shown in... Figure 6 middle.

[0067] Example 6: Fluorination at 50°C and 32 mbar for 3 minutes, with pre-cycling.

[0068] A lithium disk with a thickness of 1 mm and a diameter of 15 mm was placed in the fluorination reactor, resulting in a reduced volume. Fluorine gas (F2) was injected into the fluorination reactor at 50°C and a pressure of 32 mbar for 3 minutes. The resulting fluorinated lithium anode was then subjected to a pressure of 0.1 mA / cm². 2 and 0.2mAh / cm 2 The next cycle is repeated 1.5 times (plating-stripping-plating), followed by 2mA / cm. 2 and 1mAh / cm 2 In the next cycle, 1M LiTFSI in a 1,3-dioxolane:1,2-dimethoxyethane (1:1, by volume) electrolyte with 1-3 wt% LiNO3 added was used. The graph showing the trend of potential over time is shown in... Figure 7 middle.

[0069] Example 7: Fluorination at RT (25°C) for 30 minutes at 6 mbar, with pre-cycling.

[0070] A lithium disk with a thickness of 200 micrometers and a diameter of 15 millimeters was placed in the fluorination reactor, resulting in a reduced volume. Fluorine gas (F2) was injected into the fluorination reactor at room temperature and a pressure of 6 mbar for 30 minutes. The resulting fluorinated lithium anode was then subjected to a pressure of 0.1 mA / cm². 2 and 0.2mAh / cm 2 The next cycle is repeated 1.5 times (plating-stripping-plating), followed by 2mA / cm. 2 and 1mAh / cm 2 In the next cycle, 1M LiTFSI in a 1,3-dioxolane:1,2-dimethoxyethane (1:1, by volume) electrolyte with 1-3 wt% LiNO3 added was used. The graph showing the trend of potential over time is shown in... Figure 8 middle.

[0071] Example 8: Fluorination was performed at RT (25°C) for 10 minutes at 100 mbar without pre-cycling.

[0072] A lithium disk with a thickness of 1 mm and a diameter of 15 mm was placed in a fluorination reactor. Fluorine gas (F2) was injected into the reactor at room temperature and a pressure of 100 mbar for 10 minutes. The resulting fluorinated lithium anode was then subjected to a pressure of 1 mA / cm². 2 and 0.5mAh / cm 2 The next cycle is repeated 1.5 times (plating-stripping-plating), followed by 2mA / cm. 2 and 1mAh / cm 2 In the next cycle, 1M LiTFSI in a 1,3-dioxolane:1,2-dimethoxyethane (1:1, by volume) electrolyte with 1-3 wt% LiNO3 added was used. The graph showing the trend of potential over time is shown in... Figure 9 middle.

[0073] Example 9: Fluorination was performed at RT (25°C) for 10 minutes at 20 mbar without pre-cycling.

[0074] A lithium disk with a thickness of 1 mm and a diameter of 15 mm was placed in a fluorination reactor. Fluorine gas (F2) was injected into the reactor at room temperature and a pressure of 20 mbar for 10 minutes. The resulting fluorinated lithium anode was then subjected to a pressure of 1 mA / cm². 2 and 0.5mAh / cm 2 The next cycle is repeated 1.5 times (plating-stripping-plating), followed by 2mA / cm. 2 and 1mAh / cm 2In the next cycle, 1M LiTFSI in a 1,3-dioxolane:1,2-dimethoxyethane (1:1, by volume) electrolyte with 1-3 wt% LiNO3 added was used. The graph showing the trend of potential over time is shown in... Figure 10 middle.

[0075] Example 10: Fluorination at RT (25°C) for 3 minutes at 6 mbar, with pre-cycling.

[0076] A lithium disk with a thickness of 1 mm and a diameter of 15 mm was placed in the fluorination reactor, resulting in a reduced volume. Fluorine gas (F2) was injected into the fluorination reactor at room temperature and a pressure of 6 mbar for 3 minutes. The resulting fluorinated lithium anode was then subjected to a pressure of 0.1 mA / cm². 2 and 0.2mAh / cm 2 The next cycle is repeated 1.5 times (plating-stripping-plating), followed by 2mA / cm. 2 and 1mAh / cm 2 In the next cycle, 1M LiTFSI in a 1,3-dioxolane:1,2-dimethoxyethane (1:1, by volume) electrolyte with 1-3 wt% LiNO3 added was used. The graph showing the trend of potential over time is shown in... Figure 11 middle.

[0077] Example 11: Fluorination at RT (25°C) for 3 minutes at 0.6 mbar with pre-cycling.

[0078] A lithium disk with a thickness of 1 mm and a diameter of 15 mm was placed in the fluorination reactor, resulting in a reduced volume. Fluorine gas (F2) was injected into the fluorination reactor at room temperature and a pressure of 0.6 mbar for 3 minutes. The resulting fluorinated lithium anode was then subjected to a pressure of 0.1 mA / cm². 2 and 0.2mAh / cm 2 The next cycle is repeated 1.5 times (plating-stripping-plating), followed by 2mA / cm. 2 and 1mAh / cm 2 In the next cycle, 1M LiTFSI in a 1,3-dioxolane:1,2-dimethoxyethane (1:1, by volume) electrolyte with 1-3 wt% LiNO3 added was used. The graph showing the trend of potential over time is shown in... Figure 12 middle.

[0079] Example 12: Fluorination at RT (25°C) for 30 seconds at 6 mbar, with pre-cycling.

[0080] A lithium disk with a thickness of 1 mm and a diameter of 15 mm was placed in the fluorination reactor, resulting in a reduced volume. Fluorine gas (F2) was injected into the fluorination reactor at room temperature and a pressure of 6 mbar for 30 seconds. The resulting fluorinated lithium anode was then subjected to a pressure of 0.1 mA / cm². 2 and 0.2mAh / cm 2 The next cycle is repeated 1.5 times (plating-stripping-plating), followed by 2mA / cm. 2 and 1mAh / cm 2 In the next cycle, 1M LiTFSI in a 1,3-dioxolane:1,2-dimethoxyethane (1:1, by volume) electrolyte with 1-3 wt% LiNO3 added was used. The graph showing the trend of potential over time is shown in... Figure 13 middle.

[0081] Example 13: Fluorination at RT (25°C) for 3 minutes at 100 mbar yielded an anode for use in a complete cell with an LFP.

[0082] A clean lithium disk with a thickness of 1 mm and a diameter of 15 mm was placed in the fluorination reactor, resulting in a reduced volume. Fluorine gas (F2) was injected into the fluorination reactor at room temperature and a pressure of 100 mbar for 3 minutes. The resulting fluorinated lithium anode was then used in a complete cell with a LiFe phosphate (LFP)-based cathode at 0.204 mA / cm². 2 In the next cycle, 1M LiTFSI in a 1,3-dioxolane:1,2-dimethoxyethane (1:1, by volume) electrolyte with 1-3 wt% LiNO3 added was used. The graph relating the potential trend is shown in... Figure 14 In the figure, the changes in specific charge / discharge capacity and coulombic efficiency over time are shown in the figure. Figure 15 middle.

Claims

1. A method for surface coating of lithium metal with lithium fluoride, comprising treating the lithium metal surface with fluorine gas at a pressure between 0.5 mbar and 200 mbar and a temperature between 15°C and 80°C.

2. The method of claim 1, wherein the lithium metal is used in a 2.5 × 10⁻⁶ ppm. -9 mol fluorine / cm 2 Lithium metal with 0.51 mol fluorine / cm 2 Fluorine gas handling between lithium metals.

3. The method according to claim 2, wherein the amount of fluorine gas is 5.08 × 10⁻⁶. -9 mol fluorine / cm 2 Lithium metal with 0.255 mol / cm³ of fluorine 2 Between lithium metals.

4. The method according to any one of claims 1-3, wherein the fluorine gas is mixed with an inactive gas.

5. The method according to claim 4, wherein the inactive gas is selected from He, Ar, perfluoroalkane, and SF6.

6. The method according to any one of claims 1-3, 5, wherein the fluorine gas, or a mixture of fluorine gas and an inactive gas, is introduced into the reaction environment at a flow rate between 0.05 NL / h and 100 NL / h.

7. The method according to any one of claims 1-3 and 5, wherein the lithium metal is treated with fluorine gas for a time between 1 second and 40 minutes.

8. The method of claim 7, wherein the time is between 1 minute and 30 minutes.

9. The method according to any one of claims 1-3, 5, and 8, comprising the treatment of the lithium metal surface with fluorine gas.

Citation Information

Patent Citations

  • Cathode active material for lithium battery, lithium battery, and method for producing cathode active material for lithium battery

    EP2983230A1

  • Process for producing lithium-cobalt oxide

    US6103213A

  • Lithium iron phosphate cathode material

    US7722848B2

  • Method for preparing lithium iron phosphate nanopowder

    US9755234B2

  • Lithium-sulphur battery with high specific energy

    WO2007034243A1